Characterization of a new class of inhibitors of the recombinant human liver UDP-glucuronosyltransferase, UGT16 - Battaglia, E (Biochimica et biophysica acta, 1995)
The inhibitory effect of a series of novel structurally related compounds on the human UDP-glucuronosyltransferase UGT1*6 stably expressed in a V79 cell line was investigated. The inhibitors contain a lipophilic N-acyl phenylaminoalcohol residue and a uridine moiety connected by a spacer varying for each compound. The effects of these compounds on the glucuronidation reaction measured with 4-methylumbelliferone as substrate were determined. The best inhibitor of the series, D-DPMSU, had an IC50 of 39 microM in the assay conditions. Low Ki values were found toward both UDP-glucuronic acid and 4-methylumbelliferone (17 and 21 microM, respectively). The inhibition was competitive toward both substrates. A similar strong and competitive inhibitory effect was observed with two other inhibitors, DHPASU and DHPASiU. Another compound, D-DPASiU, showed a pure competitive inhibition towards UDP-glucuronic acid, but a non-competitive inhibition towards the acceptor substrate. These data and the optimization of the structures of the inhibitors by molecular modeling suggest that D-DPMSU and DHPASiU compounds may be transition state analog inhibitors of the recombinant UGT1*6 enzyme.